The Mass Psychology of Classroom Discourse. Issue 1 (February 2017) - Backer, David I.
Abstract: In a majority of cases observed in classrooms over the last several decades, what has gone by the name "discussion" is not discussion, but rather an interaction better known as recitation. If one sees this phenomenon as a problem, then an aspect of its resolution must be theoretical (as opposed to empirical or pedagogical): What series of conceptual terms might we adopt such that recitation does not pass for discussion? Such a theoretical response would have to address internal and external, or subjective and intersubjective, phenomena to describe what it means to participate in an interaction like discussion or recitation. Next the theory would have to explain the differences between interactions such as discussion and recitation in robust terms. Finally, these robust differences would have to prevent the "mistaking" of discussion for recitation, and vice versa. David Backer sets out to accomplish these three goals in the following essay. The theory he builds relies on a distinction between two psychological‐affective states: dehiscence and melancholia. Backer argues that recitation forms a mass through melancholic introjection of a single object, while discussion forms a group that dehiscently introjects no particular object at all. The chief finding of this essay is that viewing discussion and recitation through the mass‐psychological lens offers a new way to examine what kind of relations of influence and power form during classroom discourse and, specifically, the political significance of those discourses.